P205 Burden of anxiety and depression in the difficult asthma clinic and relationship to outcome. (15th November 2017) - Cannie, JSS; Bryce, I; MacDonald, G; Cowan, D; Brewis, M
Abstract : National Review of Asthma Deaths (NRAD) 1 stated that "there is a well-recognised link between asthma and psychosocial problems; the prevalences of anxiety, depression and panic disorder are much higher in people with asthma than in matched controls and are associated with poor outcomes." We aim to evaluate the prevalence of psychological illness within our difficult asthma clinic and its impact on asthma outcomes using data from the BTS Difficult Asthma Registry. Methods: Retrospective analysis of data submitted to the BTS Difficult Asthma Registry from July 2009 to June 2016. Outcomes were compared in those with and without anxiety or depression as defined by Hospital Anxiety and Depression (HAD) scores for each of ≥11/21. Categories for comparison included Asthma Control Questionnaire (ACQ) and Asthma Quality of Life Questionnaire (AQLQ) scores, Forced expiratory volume in one second (FEV1), Fraction of exhaled nitric oxide (FeNO), Unplanned GP/A+E attendances, Hospital Admissions, and need for oral prednisolone. Simple statistical tests such as Mann-Whitney and unpaired t tests were used to analyse the data. Results: The database included 198 individuals (68 male and 130 female), of whom 69 (35%) had anxiety and 49 (25%) had depression. There were no statistically significant differences between each group for FEV1, FeNO and peripheral eosinophil count. Anxiety was associated with higher ACQ and lower AQLQ scores than non-anxiety (4 vs 2.8 and 2.9 vs 3.8 respectively, both p<0.0001) and increased number of steroid boosts per year (6 vs 5, p=0.013). Depression was associated with higher ACQ and lower AQLQ scores than non-depression (p<0.0001) and increased number of steroid boosts per year (6 vs 5, p=0.021). Conclusions: There is a high prevalence of anxiety and depression in the difficult asthma clinic, and both co-morbidities are associated with a greater symptom burden and an increased number of steroid boosts per year not explained by objective measures of asthma control. Further research is required to evaluate the impact of clinical psychology in this setting. Reference: NRAD – https://www.rcplondon.ac.uk/projects/outputs/why-asthma-still-kills